Drip vs. Mini-sprinkler Irrigation System on Leaf Water Potential and Various Vegetative Attributes of Annona squamosa under Lebanese Conditions - May Hammoud; Saleh Mobarak Alturk; Zeina El Sebaaly; Youssef Najib Sassine (AGRIVITA, Journal of Agricultural Science, 2021)
Recently, the introduction of tropical crops in Lebanon represented a challenge for farmers and researchers. Constraints to the adaptation of such crops, to climatic and soil conditions were found. In this study, an orchard of Annona trees (Sq/Ch combination) was irrigated by minisprinkler system and drip system, and compared to a control (not irrigated) over two consecutive years (year 4 and year 5 of the project). Compared to the control, plant height and leaf number were improved the most in year 5 by drip irrigation. Leaf water potential that peaked in the summer season in control plants (-1.8 MPa) was the lowest in plants irrigated by drip system (-1.3 MPa). No significant difference was observed between treatments in the number of lateral shoots. TDM of plant parts was improved by drip irrigation in both experimental years by 81 g (year 4) and by 258 g (year 5). LMF was significantly enhanced in year 5 by the mini-sprinkler system. RMF was the highest in trees irrigated by drip irrigation (0.265 g/g) and the lowest in the control (0.227 g/g). SMF was the highest in control trees in both experimental years. It seems that drip system presented an optimal method for the irrigation of annona.